Mesoporous Zeolitic Materials (MZMs) Derived From Zeolite Y Using a Microwave Method for Catalysis - Abdulridha, Samer; Jiao, Yilai; Xu, Shaojun; Zhang, Rongxin; Garforth, Arthur A.; Fan, Xiaolei (Frontiers in Chemistry, 2020)
Mesostructured zeolitic materials (MZMs) with the relatively high acidity (both Lewis and Brönested ones in comparison with the mesoporous siliceous MCM-41) were prepared via an efficient, mild and simple post-synthetic treatment (of Y zeolite) method facilitated by the microwave irradiation, i.e. microwave-assisted chelation (MWAC). The disordered mesoporous aluminosilicates materials (DMASs) of MZM were created from Y zeolite in the absence of using mesoscale templates. The prepared mesoporous materials showed the significant mesoporous features with the mesopore area and volume of ~260 m2 g−1 and ~0.37 cm3 g−1, respectively, and with the mesopore sizes distributed in a range of 2.5–15 nm. MZM materials possess the total acidity of about 0.6 mmol g−1, and exhibited comparatively superior catalytic activity to the parent Y zeolite and MCM-41 in the vapor-phase catalytic dealkylation of 1,3,5 triisopropylbenzene (TiPBz) and liquid-phase catalytic aldol condensation (of benzaldehyde with 1-heptanal). Although the yield loss is inevitable for preparing MZMs using the MWAC method, the preliminary economic analysis of the preparation cost of MZMs is reasonable. Additionally, a comprehensive comparison of the state-of-the-art mesoporous materials concerning their sustainable aspects was made, showing that MZMs are promising mesoporous materials for further development and functionalisation for catalysis.